PRACTICAL CLASSES IN HIGHER EDUCATION INSTITUTIONS AS A FACTOR ENSURING THE PROFESSIONAL TRAINING OF UNDERGRADUATE MATHEMATICS STUDENTS - A. Abdirahmonov (International Journal of Literature and Language Studies, 2026)
This article analyzes the role of practical classes organized in higher education institutions in the formation of the professional competencies of future mathematicians studying in undergraduate programs. The significance of practical classes in strengthening theoretical knowledge, developing logical thinking, forming problem-solving skills, and improving professional training based on modern pedagogical technologies is highlighted. The research findings demonstrate that practical classes are an important factor in improving the quality of education and enhancing the professional potential of future specialists.